Zwei Himmel - zwei Körper: zur paracelsischen Kosmologie im astrologischen Tagesschrifttum - Pfister, Kathrin (Daphnis, 2020)
This article focuses on Paracelsus as an astrologer and the development of his cosmology in his intra-vitam publications. Paracelsus seems to have used his astrological writings as a testing ground to present his heterodoxical concept of the two heavens and two bodies to the public. The article also traces the reappearance of these ideas in practicas and calendars in the 17th century.
Gesehen am 05.10.2022